Cooperative Processing with Multi-Robot Systems - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, AIM, 2017)
Multi-robot systems are increasingly utilized for cooperative industrial robot applications. In the scope of this work, a novel approach for the division of robot applications between multiple robots by handling the tool and the workpiece at the same time is presented. The approach has been tested successfully with a robot setup with two industrial robot arms. It is shown that the processing time can be reduced and the reachability can be improved by the developed approach. In order to compensate complex programming of the cooperative tasks, an automatic programming is also realized. Thus, the programming time can be significantly reduced.
CRIS-Team Scopus Importer:2023-03-07